OP0259-HPR Supervised walking improves aerobic capacity, exercise tolerance, fatigue and perceived improvement in women with primary sjÖgren's syndrome: a randomized controlled trial. (15th June 2017) - Miyamoto, ST; Valim, V; Carletti, L; Ng, W-F; Altoé, R; Perez, AJ; Dias, LH; Serrano, ΈV; Subtil, AM; Cândido, VB; Trenell, M; Lendrem, D; et al.
Abstract : Background: Fatigue is a very common symptom of primary Sjögren's syndrome (pSS), being reported by up to 70% of patients [1]. It is more pronounced when compared to healthy individuals [2] and patients often report that it is their greatest problem and the most difficult to cope with [3]. There is only one non-randomized controlled study on aerobic exercise in pSS with a small sample size suggesting improvement in fatigue, aerobic capacity, depression and physical function [4]. Objectives: To evaluate the safety and effectiveness of a supervised walking program in women with pSS. Methods: Forty five sedentary women fulfilling the American European Consensus Criteria for pSS were randomized to a Training Group (TG, n=23) or Control Group (CG, n=22). Patients in the TG were submitted to supervised walking, 3 times a week, for 16 weeks. The patients of the CG were instructed to not perform any kind of regular physical exercise. Outcomes measured were aerobic capacity, fatigue, disease activity, depression, perception of pSS's symptoms and quality of life. An intent-to-treat analysis was performed. Results: The mean change after 16 weeks of VO2max (ml.kg -1 .min -1 ), distance and FACIT-fatigue were higher in the TG than in the CG (p=0.016, p=0.043 and p=0.030, respectively) (Figure 1 ). Improved aerobic capacity was associated with improvements in fatigue scores and physical components of quality of life measured using SF-36. Furthermore, improved fatigue scores were associated with reduced depression and improvements in the physical and mental components of the quality of life measures. Overall, 95.4% of patients in the TG rated themselves as clinically improved versus 62% of the patients in the CG (p=0.049). There was no flare in disease activity and no serious adverse events with exercise. Conclusions: This supervised walking program was demonstrated to be feasible and safe with improvements in the aerobic capacity, exercise tolerance, fatigue and patient perception of improvement in pSS patients. References: Ng W-F, Bowman SJ. Primary Sjogren's syndrome: too dry and too tired. Rheumatology 2010;49(5):844–53. Strömbeck B, Ekdahl C, Manthorpe R, et al. Physical capacity in women with primary Sjögren's syndrome: a controlled study. Arthritis Rheum 2003;49(5):681–8. Meijer JM, Meiners PM, Huddleston Slater JJR, et al. Health-related quality of life, employment and disability in patients with Sjogren's syndrome. Rheumatology 2009;48(9):1077–82. Strömbeck BE, Theander E, Jacobsson LTH. Effects of exercise on aerobic capacity and fatigue in women with primary Sjogren's syndrome. Rheumatology 2007;46(5):868–71. Acknowledgements: This work was supported by the Coordenação de Aperfeiçoamento de Pessoal de Nível Superior - CAPES Foundation [BEX 8831/14–9 to S.T.M]. Disclosure of Interest: None declared